Rethinking Language Education in Indonesia - Maslihatul Umami (UIN Salatiga, 2008)
Language education in Indonesia may be discussed by over viewing the nature of the three language categories in the country: Indonesian language, indigenous languages, and foreign languages. From the picture of how the three groups of languages work and function, the problem raised in this paper is based on two fundamental assumptions. Language education in this multilingual and multicultural country is not done on the context of literacy, on the one hand, and it is not yet considered important in comparison with that of the subjects related to basic science and technology, on the other. After reviewing a number of models of bilingual education and comparing them with what has been done in Indonesia, a preferred model will be offered. Finally, it will also be suggested that language education in Indonesia should be associated with literacy development in a wider sense. Furthermore, meanwhile language education should be given an adequate room; language teaching should be based on the functional use of the existing languages in the country and should be done in tandem with the teaching of content since content is delivered through the medium of language. Keywords: education; language function; literacy development; content